Kesan in vitro rilmenidine ke atas rembesan insulin - Rosnani Hashim,; Tariq Abdul Razak,; Suhaimi Hashim, (penerbit ukm, 2003)
This study was carried out to determine the in vitro effect of a new antihypertensive drug, Rilmenidine, on insulin secretion. The direct effect of Rilmenidine on glucose-induced insulin secretion was studied using isolated rat pancreas. The concentrations of Rilmenidine used were based on the peak plasma concentration achieved with an oral dose of 1 mg. T a low concentration, Rilmenidine (0.35 ng/ml) significantly stimulated insulin secretion (p‹0.01). However, Rilmenidine showed a significantly weak inhibition (p< 0.05) at 3.5 ng/ml and a strong inhibitin at a higher concentration (35.0 ng/ml). The result showed that Rilmenidine exhibited significant stimulating and inhibitory effects on insulin secretion from the pancreas at different concentrations.